PENERAPAN YURISDIKSI MAHKAMAH PIDANA INTERNASIONAL DALAM UPAYA PERLINDUNGAN TERHADAP HAK ASASI MANUSIA PADA KONFLIK BERSENJATA NASIONAL - Danel Aditia Situngkir (Ensiklopedia Social Review, 2025)
Abstract: This research raises the title regarding the Application of the Jurisdiction of the International Criminal Court in Efforts to Protect Human Rights in National Armed Conflicts. Implementation means the process or way of making. Jurisdiction can generally be interpreted as legal authority over certain people, bodies or events within a certain territorial scope. The International Criminal Court is the First Permanent International Criminal Court established under the Rome Statute. Protection efforts are defined as actions and so on to provide protection). Human rights are the most basic rights that humans have as creatures created by God. Conceptually, in this research, what will be discussed is the process or method of applying the authority of the International Criminal Court to people in certain incidents as an effort to protect human rights.Keywords: Application, Jurisdiction of the International Criminal Court, Human Rights.